Zwart in de beeldhouwkunst (het). - ATELIER 340 (Brussel : Atelier 340, 1993)
Gheerardijn, Jean-Marie ; Hamelryck, Ado ; Huby, Simone ; Leblanc, Walter ; Tapta ; Bogart, Bram ; Broodthaers, Marcel ; Claus, Christian ; Coeckelberghs, Luc ; Copers, Leo ; Cortier, Amédée ; Feulien, Marc ; Flament, Richard ; Freson, Florence ; Gentils, Vic ; Lafontaine, Marie-Jo ; Marx, Dominique ; Vrolix ; Canogar, Rafael ; Luther, Adolf ; Nevelson, Louise ; Prantl, Karl ; Soulages, Pierre ; Venet, Bernar
18.06-17.10.1993
boek